Sector-Specific Strategies: How Consumer Goods Companies Navigate Tax Avoidance - Djatnicka, Erlina; Sulistyorini Wulandari, Dian; Dayanti, Iis (Journal of International Multidisciplinary Research, 2024)
This research aims to investigate the impact of transfer pricing, thin capitalization, and capital intensity on tax avoidance within the consumer goods industry. The study focuses on how these key financial strategies are employed by companies to reduce their tax liabilities while navigating complex global tax environments. Transfer pricing allows companies to shift profits across jurisdictions by manipulating the prices of intra-company transactions, while thin capitalization—the practice of using excessive debt relative to equity—enables companies to maximize interest deductions and lower taxable income. Capital intensity, defined as the ratio of capital assets to sales, also plays a crucial role, as firms with significant physical assets can benefit from tax deductions through depreciation, further reducing taxable obligations. The sample used in this study was selected using purposive sampling, resulting in 23 companies that have complete financial reports and meet the specified criteria. By analyzing financial data and company reports, this research provides insights into sector-specific tax strategies and discusses the ethical implications, sustainability, and regulatory challenges associated with these practices in the consumer goods sector. The analysis shows that transfer pricing negatively and significantly affects tax avoidance, indicating that more aggressive transfer pricing practices may actually reduce tax avoidance activities. In contrast, thin capitalization and capital intensity do not show a significant impact on tax avoidance.